2007
DOI: 10.1007/s10695-007-9179-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative role of selenium against the toxic effect of heavy metals (Cd+2, Cr+3) on liver of rainbow trout (Oncorhynchus mykiss Walbaum 1792)

Abstract: The main purpose of this study is to discuss the effect of Cd+2, Cr+3 and Se metals on biochemical parameters in liver tissue of Oncorhynchus mykiss. The rainbow trout were exposed to heavy metal stress (Cd+2, Cr+3) at 2 ppm dosage. The present study was undertaken to determine the protective effect of selenium treatment at the same dosage (2 ppm) on some biochemical parameters. The activity of catalase (CAT), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and the changes in levels of malondialdeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 29 publications
2
24
2
1
Order By: Relevance
“…GPx inhibition was also reported by Oruç and Ü ner (2000) in livers of the Nile tilapia Oreochromis niloticus after combined treatment with the herbicide 2,4-dichlorophenoxyacetic acid and the insecticide azinphosmethyl. Furthermore, Talas et al (2008) observed a marked depletion in GPx activity in the liver of Oncorhynchus mykiss after exposure to Cd and Cr. Pandey et al (2001) detected a decrease in GPx and GST activities after exposure to Cu in Channa punctatus, and Dupuy and Szabo (1986) documented significant decreases in rat cysteine levels following Cu exposure.…”
Section: Discussionmentioning
confidence: 89%
“…GPx inhibition was also reported by Oruç and Ü ner (2000) in livers of the Nile tilapia Oreochromis niloticus after combined treatment with the herbicide 2,4-dichlorophenoxyacetic acid and the insecticide azinphosmethyl. Furthermore, Talas et al (2008) observed a marked depletion in GPx activity in the liver of Oncorhynchus mykiss after exposure to Cd and Cr. Pandey et al (2001) detected a decrease in GPx and GST activities after exposure to Cu in Channa punctatus, and Dupuy and Szabo (1986) documented significant decreases in rat cysteine levels following Cu exposure.…”
Section: Discussionmentioning
confidence: 89%
“…Negative correlations were found between CAT activity and MDA levels. Lipid peroxidation, considered a complex selfpropagating process producing high levels of cell degradation, increases the rigidity (decreases the fluidity) of cellular membranes (Ates et al 2008;Talas et al 2008). Table 1 shows the results of the biochemical analysis of the carp stored at the selling conditions (9-12°C) in the laboratory in relation to storage time post-slaughter.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the fat content of the diet may lead to a higher level of non-enzymatic antioxidants, thereby increase the Se requirement. Moreover, most previous experiments in dietary Se requirements for rainbow trout and Atlantic salmon were conducted using mineral Se (Hilton et al, 1980;Bell et al, 1986Bell et al, , 1987Talas et al, 2008). This has been reported to have lower bioavailability and trophic transfer properties compared with organic Se (selenomethionine) (Lorentzen et al, 1994;Wang and Lovell, 1997;Fan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%